SENSITIVITAS FAKTOR EKONOMI MAKRO DAN MIKRO DALAM MEMPREDIKSI VOLATILITAS HARGA SAHAM PERUSAHAAN SEKTOR INDUSTRI FOOD & BEVERAGES - Abdul Kohar; Nurmala Ahmar; Suratno Suratno (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2018)
The movement of macroeconomic factors can be used to predict the movement of the stock price, but different researchers are using different macroeconomic factors because there is still no consensus among them which macroeconomic factors that have an influence on stock prices. This study aimed to analyze and test the impact of macroeconomics factors which consisting of inflation, interest rates, exchange rate, and microeconomy factors, consisting of asset growth, growth earnings and sales growth to the volatility of stock prices on food and beverages companies listed in Indonesia Stock Exchange between 2011 and 2015 period. The study measure the sensitivity of inflation and interest rates and stock price volatility by regressing each variable with a share price which will produce the sensitivity value of each variable. A total of 66 samples are tested by using the classic assumption as the precondition for regression analysis techniques (multiple regressions). The results showed that inflation is partially affect the stock price volatility, Indonesia Interest Rate (SBI) is partially effect on stock price volatility, and exchange rate and microeconomics are partially no effect on stock price volatility.